2016
DOI: 10.4103/0973-1482.176412
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of florine-18 fluorodeoxyglucose/positron emission tomography/computed tomography imaging in well-differentiated thyroid cancers with negative iodine-131 scan high thyroglobulin and normal anti-thyroglobulin levels

Abstract: FDG PET/CT imaging is a valuable imaging method in the evaluation of patients with elevated serum Tg levels and normal anti-Tg levels. Furthermore, it has potential utility in the dedifferentiation of active foci that are present, and in assessing optimal decision making during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Several studies have previously established the increasing sensitivity of FDG-PET exams [4,5,7,10,17,20]. The cutoff value most widely agreed on in literature and included in the current ATA guidelines [11] is set at 10 ng/ml.…”
Section: Subgroup Of Patients With Elevated Stg (≥ 10 Ng/ml)mentioning
confidence: 99%
“…Several studies have previously established the increasing sensitivity of FDG-PET exams [4,5,7,10,17,20]. The cutoff value most widely agreed on in literature and included in the current ATA guidelines [11] is set at 10 ng/ml.…”
Section: Subgroup Of Patients With Elevated Stg (≥ 10 Ng/ml)mentioning
confidence: 99%
“…The remaining 97 articles were carefully assessed by full-text and another 80 were excluded for the following reasons: case reports, abstracts, letters, reviews or meta-analysis (n = 8); articles not available or not in English (n = 2); data not retrievable for analysis (n = 33); insufficient reference standard (n = 1); less than 10 patents (n = 3); PET study without CT (n = 31) and with only scan-based data (n = 2). Finally, 17 articles (21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37) including data on the diagnostic performance of 18 F-FDG-PET/CT in DTC patients with thyroglobulin elevation and negative iodine scintigraphy were eligible for further analysis. A PRISMA flow diagram of the study selection process is shown in Fig.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%